Minority report : Mennonite identities in imperial Russia and Soviet Ukraine reconsidered, 1789-1945 - Friesen, Leonard G. (Tsarist and Soviet Mennonite studies., 2018)
In Minority Report, Leonard G. Friesen and the volume's contributors boldly reassess Mennonite history in Imperial Russia and the former Soviet Ukraine.